Clinical relevance of FOXP3, PD-L1, PD-1, and miR-155 gene expression and genetic variants in HPV-negative oral carcinomas - Ivkovic, Nemanja; Misic, Debora; Kozomara, Ruzica; Jovic, Sasa; Šami, Ahmad; Velikic, Gordana; Stosic, Srboljub; Supic, Gordana (International journal of molecular sciences, 2025)
PD-L1, PD-1, FOXP3, and miR-155 are emerging as key modulators of immune evasion and progression of oral squamous cell carcinoma (OSCC). This study investigated the clinical relevance of their gene expression and variants in HPV-negative OSCC. Bulk-tissue mRNA expression was evaluated in 70 patients, while variants in PD-1 (rs36084323), PD-L1 (rs822336, rs4143815, copy number variation), FOXP3 (rs3761548, rs2232365), and miR-155 (rs767649) were assessed in 134 patients. Expression data were validated using the TCGA cohort of 222 HPV-negative OSCC cases. Low FOXP3 expression was significantly associated with tumor stage (MMA: p = 0.028, TCGA: p = 0.025) and poor overall survival (MMA: p = 0.0004, TCGA: p = 0.019) in both cohorts. Declining FOXP3 expression correlated with advancing tumor stages, and low FOXP3 expression was significantly associated with poor survival in advanced stage III-IV tumors (MMA: p = 0.001, TCGA: p = 0.015), but not early-stage tumors. High miR-155 expression was associated with recurrence (p = 0.002) and poor survival in the MMA (p = 0.007), but not TCGA cohort. MiR-155 rs767649 was associated with alcohol consumption (p = 0.018). These findings point to FOXP3 and miR-155 as potential prognostic biomarkers for HPV-negative OSCC. Stage-specific FOXP3 expression suggests a dynamic immunoregulatory role, with implications for optimizing immunotherapy timing. Further studies are warranted to resolve cellular context and stage-adapted immune interventions in HPV-negative OSCC.